Colorimetric gas detection by the varying thickness of a thin film of ultrasmall PTSA-coated TiO2 nanoparticles on a Si substrate - Joost, Urmas; Šutka, Andris; Visnapuu, Meeri; Tamm, Aile; Lembinen, Meeri; Antsov, Mikk; Utt, Kathriin; Smits, Krisjanis; Nõmmiste, Ergo; Kisand, Vambola (Beilstein-Institut Zur Forderung der Chemischen Wissenschaften, 2017)
Colorimetric gas sensing is demonstrated by thin films based on ultrasmall TiO2 nanoparticles (NPs) on Si substrates. The NPs are bound into the film by p-toluenesulfonic acid (PTSA) and the film is made to absorb volatile organic compounds (VOCs). Since the color of the sensing element depends on the interference of reflected light from the surface of the film and from the film/silicon substrate interface, colorimetric detection is possible by the varying thickness of the NP-based film. Indeed, VOC absorption causes significant swelling of the film. Thus, the optical path length is increased, interference wavelengths are shifted and the refractive index of the film is decreased. This causes a change of color of the sensor element visible by the naked eye. The color response is rapid and changes reversibly within seconds of exposure. The sensing element is extremely simple and cheap, and can be fabricated by common coating processes.
Financial support from the Estonian Research Council (IUT2-25, PUT170, PUT1096, PUT748, PUTJD680), the Estonian Centre of Excellence in Research Projects “Advanced materials and high-technology devices for sustainable energetics, sensorics and nanoelectronics” TK141 (2014-2020.4.01.15-0011), “Emerging orders in quantum and nanomaterials” TK134 and the Development Fund of the University of Tartu, are all gratefully acknowledged.
Keywords: colorimetric gas sensing; p-toluenesulfonic acid (PTSA); TiO2 nanoparticles; Research Subject Categories::NATURAL SCIENCES:Physics